HUBUNGAN ANTARA KETERLIBATAN KARYAWAN DALAM PROSES PERUBAHAN DENGAN KESIAPAN MEREKA MENGHADAPI PERUBAHAN: STUDI PADA DIVISI SALES PT. ABC - Hervina Andriani; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2017)
Policy change and work system is frequently required for organization to keep competitive. Problem raised when employees express lack of readiness to change. PT. ABC is one among the company which deal with this problem. As one of shoes and bags company, PT. ABC make changes to commission and incentives system. The company expects the change will encourage employees to make sales according to predetermined targets to earn higher commissions compared to the old system. However, in the other side employees actually feel aggrieved because they lost the opportunity to get a commission. The research was conducted to 80 employees of sales division of PT. ABC spread across Indonesia using quantitative and qualitative approach. Questionnaires were implemented in the quantitative approach, that measure (1) involvement in the change process and (2) readiness to change. Interviews were conducted in the qualitative approach with three respondents whose involvement and readiness scores were high and low. Results showed there was a positive relationship between the involvement in the change process with the readiness to changes shown by the Spearman correlation coefficient of 0.625 with p